Inhibition of microRNA-449a prevents IL-1β-induced cartilage destruction via SIRT1. Issue 12 (December 2016) - Park, K.W.; Lee, K.-M.; Yoon, D.S.; Park, K.H.; Choi, W.J.; Lee, J.W.; Kim, S.-H.
Summary: Objective: SIRT1 has anti-inflammatory as well as protective effects in chondrocytes. The object of this study was to investigate whether microRNA-449a regulates expression of SIRT1, which inhibits expression of catabolic genes in IL-1β-induced cartilage destruction. Materials and methods: MicroRNA-449a expression was determined in OA chondrocytes and IL-1β-induced chondrocytes by real-time PCR. MicroRNA-449a binding sites on the 3′-UTR of SIRT1 mRNA and binding site conservation were examined using microRNA target prediction tools. SIRT1-overexpressing or knockdown chondrocytes were transfected with microRNA-449a or anti-microRNA-449a mimic and stimulated by IL-1β. Expression of catabolic and anabolic genes was examined by real-time PCR and western blotting. Finally, positive effects of anti-microRNA-449a on expression of these genes were confirmed by western analysis of OA chondrocytes. Results: Expression of microRNA-449a was increased in OA chondrocytes and IL-1β-induced chondrocytes. MMP-13 expression was enhanced, whereas type II collagen and SIRT1 expression were decreased in IL-1β-induced chondrocytes. SIRT1 overexpression resulted in decreased expression of catabolic genes such as MMPs and ADAMTSs in response to IL-1β, but these effects were moderated by microRNA-449a. Suppression of microRNA-449a by anti-microRNA-449a inhibited expression of catabolic genes despite IL-1β stimulation, but these effects were abolished in SIRT1 knockdown chondrocytes. Furthermore, expression of catabolic genes was decreased and expression of type II collagen as well as SIRT1 was restored by anti-microRNA-449a in OA chondrocytes as well as in IL-1β-induced chondrocytes. Conclusion: Silencing of microRNA-449a had a protective effect, inhibiting catabolic gene expression and restoring anabolic gene expression, by targeting SIRT1 in IL-1β-induced cartilage destruction.